2016
DOI: 10.1186/s12859-016-1397-7
|View full text |Cite
|
Sign up to set email alerts
|

acdc – Automated Contamination Detection and Confidence estimation for single-cell genome data

Abstract: BackgroundA major obstacle in single-cell sequencing is sample contamination with foreign DNA. To guarantee clean genome assemblies and to prevent the introduction of contamination into public databases, considerable quality control efforts are put into post-sequencing analysis. Contamination screening generally relies on reference-based methods such as database alignment or marker gene search, which limits the set of detectable contaminants to organisms with closely related reference species. As genomic cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Quality-filtered reads were assembled using SPAdes 3.10.0 with the –sc option and kmer sizes 21, 25, 33, 37, 43, 47, 51, 55, 59, 63, 67, 71, 73, 79, 81, and 85. Contaminant screening was performed using the Automated Contamination Detection and Confidence (ACDC) software ( 90 ), which categorizes contigs based on GC content and tetranucleotide frequency. The assembly of well 657K04 was found to have two 16S rRNA gene sequences, indicating that two cells may have been sorted and amplified in one well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality-filtered reads were assembled using SPAdes 3.10.0 with the –sc option and kmer sizes 21, 25, 33, 37, 43, 47, 51, 55, 59, 63, 67, 71, 73, 79, 81, and 85. Contaminant screening was performed using the Automated Contamination Detection and Confidence (ACDC) software ( 90 ), which categorizes contigs based on GC content and tetranucleotide frequency. The assembly of well 657K04 was found to have two 16S rRNA gene sequences, indicating that two cells may have been sorted and amplified in one well.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the 16S rRNA sequences was identical to single-cell genomes 657A03 and 662N06, respectively. Using the ACDC software ( 90 ), we observed that tetranucleotide frequencies and GC content were sufficient to separate the two genomes in assembly 657K04 (see Fig. S2 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…Before running the pangenome analysis, contamination in the genomes was assessed with acdc (51). Genomes with unusual gene content or genome size identified during the pangenome analysis and suspected of possible contamination were analyzed to identify contamination and remove any suspected instances where contaminant sequences were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Paired-end reads were extracted from the binned scaffolds using extract.fastq.for.reassembly.pl (37) and were used for reassembly using SPAdes version 3.10.1 (48), with k values of 21, 33, 55, and 77, as recommended for PE 2 ϫ 150-bp reads (48). Assembly coverage, GC content, and/or tetranucleotide frequencies were used for an additional round of screening with mmgenome, and assemblies were run through the online web tool for ACDC (49) to remove suspected contaminants. Genome completeness and contamination were estimated with CheckM (11).…”
Section: Methodsmentioning
confidence: 99%